Schizophreniform Disorder Related Hospitalizations: A Clinical and Demographic Analysis of a National Hospitalization Database - Teixeira da Cunha, Inês (2024)
Introduction: Schizophreniform disorder manifests itself with similar symptoms to schizophrenia, but it is distinguished from the latter by its shorter duration, varying between at least one and six months. This study aimed to describe and analyze schizophreniform disorder related hospitalizations in a national hospitalization database.Methods: We planned a descriptive retrospective study using a nationwide hospitalization database containing all hospitalizations registered in Portuguese mainland public hospitals from 2008 to 2015. Hospitalizations with a primary diagnosis of schizophreniform disorder were selected based on the International Classification of Diseases version 9, Clinical Modification (ICD-9-CM) code of diagnosis 295.4x. Data regarding birth date, sex, residence address, diagnoses, length of stay, discharge status, and hospital charges were obtained. Comorbidities were analyzed using the Charlson Index Score. Independent Sample t tests were performed to assess differences in continuous variables with a normal distribution and Mann-Whitney-U tests when no normal distribution was registered.Results: In Portuguese mainland public hospitals, a total of 594 hospitalizations with a primary diagnosis of schizophreniform disorder occurred during the eight-year study period. Most, 72.1% (n = 428), were observed in male patients. The mean age at admission was 34.34 years in male patients and 40.19 years in female patients. The median length of stay was 17.00 days and in-hospital mortality was 0.5% (n = 3). Only 6.1% (n = 36) of the hospitalization episodes had one or more registered comorbidities. Forty-one readmissions were documented.Conclusion: Hospitalizations with a primary diagnosis of schizophreniform disorder occur more frequently in young male patients. This is, to the best of our knowledge, the first nationwide study analyzing all hospitalizations due to this diagnosis in Portugal.